Physical activity, from common-sense essence to ancient problematisation, definition, interpretation and guidance - Stefanović Đorđe (Fizička Kultura)
This paper examines physical activity and exercise as used for the health of the ancient Greeks. Records and testimonies from philosophers, trainers, physicians, athletes... guided people toward improving vitality through exercise. These sources contain historical facts relating to the maintenance of individual physical, psychological, social and affective health through movement and exercise. Conclusions about the continuous relationship between direct physical activity and exercise (PAE) and physical exercise and health (PEH) were reached through multifaceted analysis (historical, comparative, causal, semantic) and synthesis, as well as inductive and deductive reasoning. The subject of this paper is the common-sense recognition and deliberation on the significance of PAE for human health during the paleo society, its problematisation and application in practice leading to PEH. The starting premise is cognitively provocative, referring to the origins and utility of paleo science and practice in today's understanding and practice of PAE and PEH. Paleo philosophers believed that PAE, only in optimal amounts, i.e., the "measure of common-sense moderation, " can have a beneficial, positive effect on a healthy lifestyle for humans/athletes. Their frequent critical views on deviations from the common-sense essence of PEH were directed towards preserving the benefits of a healthy lifestyle-PEH. They believed that common sense (bon sens) represents the fundamental axiom for the development of "practical science, " through which the problems of the life of an individual, society and nature were understood, solved, and guided. Philosophers, physicians, and trainers were the most knowledgeable about the importance of PAE for a healthy lifestyle of an individual in ancient Greece! The second premise, although sporadically considered in this paper, contains meaning and expression for provoking modern science and practice of PAE and PEH, pointing out that there is a current tendency of individuals to relinquish the common-sense nature of exercise in favour of personal prophylaxis. The conclusion is that despite sometimes "aggressive" efforts of the society to institutionalise PAE to PEH, individuals continue to seek the factors of health, sustainability and survival (conditio humana). Although direct and simple life activity, PEH appears to be an unknown determinant of the quality of life, as if theories on nature and nurture in human development through PAE are not truthful.